Analisis Diplomasi Olahraga Small Island Developing States Pada Piala Dunia FIFA 2026: Studi Kasus Tanjung Verde - Noor Fahmi Pramuji; Anastazia Niatri Wattimena (Journal of International and Local Studies, 2026)
This study investigates the public diplomacy strategy of Cape Verde, a Small Island Developing State (SIDS), in leveraging its participation in the FIFA World Cup 2026 as an instrument of sports diplomacy, nation branding enhancement, and soft power projection. Existing sports diplomacy literature has predominantly focused on developed nations or mega-event hosts, leaving an academic gap regarding how micro-states convert sporting visibility into soft power without hosting the event. Employing Stuart Murray's Sports Diplomacy framework and Joseph Nye's Soft Power concept, this qualitative exploratory case study analyzes Cape Verde's optimization of diaspora networks and nation branding. Findings indicate that Cape Verde effectively utilizes its national football team as a track-two diplomacy actor to project resilience, redefine its national identity to a global audience, and its impressive achievements act as a nation-branding catalyst that transcends its traditional diplomatic capabilities. So, sports diplomacy allows SIDS to pierce the asymmetry of the international system and transform structural vulnerabilities into cultural attractions (soft power) with geopolitical stability implications. Traditional resource constraints are mitigated through culturally driven niche diplomacy.